2017
DOI: 10.1016/j.jmu.2016.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Evolving Cesarean Scar Pregnancy into Morbidity Adherent Placenta—Evidence from Serial Ultrasound Examination

Abstract: Objective:To present the complete history of a case with placenta accreta and demonstrate the special clues of ultrasonography finding during whole trimesters from early pregnancy to delivery.Case Report:A multiparous 28-year-old female with a history of multiple cesarean deliveries was found with suspected precesarean section scar pregnancy at 6 weeks of gestation. We performed a series of ultrasonography scans, which revealed placenta previa totalis and placenta accreta at 15 and 32 weeks of gestation, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The only possible justification of this may that in fresher scars the granulation tissue and scar itself may be a feasible or attractive site for MAP while the older scars may have changed physiologically so much that it would not favor the development of MAP and can be further examined. According to literature, the earliest gestation at which placenta accreta had been diagnosed by ultrasound was 9 weeks in a case of scar pregnancy [18][19][20] . Vijayasree M 2018 21 in the study, revealed sonography was only 33-percent sensitive for detecting placenta accrete.…”
Section: Resultsmentioning
confidence: 99%
“…The only possible justification of this may that in fresher scars the granulation tissue and scar itself may be a feasible or attractive site for MAP while the older scars may have changed physiologically so much that it would not favor the development of MAP and can be further examined. According to literature, the earliest gestation at which placenta accreta had been diagnosed by ultrasound was 9 weeks in a case of scar pregnancy [18][19][20] . Vijayasree M 2018 21 in the study, revealed sonography was only 33-percent sensitive for detecting placenta accrete.…”
Section: Resultsmentioning
confidence: 99%
“…However, it has been reported that, especially at earlier stages, CSP may be only mildly symptomatic, with no typical clinical findings, resulting in a late diagnosis and treatment and more severe outcomes [20]. Thus, to avoid a delayed or missed diagnosis and to improve diagnostic efficiency, TVUS is usually performed at early pregnancy stages in patients with an history of previous uterine surgery or cesarean sections [21,22]. The sensitivity of TVUS for diagnosing cesarean scar pregnancies is reported to be 84.6% [23], and it is still the preferred imaging method.…”
Section: Discussionmentioning
confidence: 99%
“…No clear treatment guidelines have been suggested for the treatment of Morbidly Adherent Placenta. It has been shown that if cesarean scar pregnancy is complicated with morbidly adherent placenta (cesarean scar adherent placental tissue invasion), the most frequently therapeutic approach is hysterectomy [9].…”
Section: Discussionmentioning
confidence: 99%